2020
DOI: 10.1186/s12890-020-01236-1
|View full text |Cite
|
Sign up to set email alerts
|

Do-not-resuscitate orders in patients with community-acquired pneumonia: a retrospective study

Abstract: Background: To investigate the use of do-not-resuscitate (DNR) orders in patients hospitalized with communityacquired pneumonia (CAP) and the association with mortality. Methods: We assembled a cohort of 1317 adults hospitalized with radiographically confirmed CAP in three Danish hospitals. Patients were grouped into no DNR order, early DNR order (≤48 h after admission), and late DNR order (> 48 h after admission). We tested for associations between a DNR order and mortality using a cox proportional hazard mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…Patients with EDNR had lower 7-, 30-, and 90-day survival; our finding is compatible with another study where EDNR was found to be an independent predictor for 28-day mortality [7]. In a Danish cohort of patients with community acquired pneumonia (CAP), EDNR was associated with higher mortality after adjustment for clinical risk factors [16]. Among intracerebral hemorrhage (ICH) patients, EDNR is an independent predictor of poor outcome [30,31]; 2.6 times more likely to die than those without DNR order [30].…”
Section: Survivalsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients with EDNR had lower 7-, 30-, and 90-day survival; our finding is compatible with another study where EDNR was found to be an independent predictor for 28-day mortality [7]. In a Danish cohort of patients with community acquired pneumonia (CAP), EDNR was associated with higher mortality after adjustment for clinical risk factors [16]. Among intracerebral hemorrhage (ICH) patients, EDNR is an independent predictor of poor outcome [30,31]; 2.6 times more likely to die than those without DNR order [30].…”
Section: Survivalsupporting
confidence: 89%
“…Similarly, a Danish cohort of patients with community-acquired pneumonia (CAP) found patients with EDNR were older and more frequently nursing home residents (41% vs. 6%, p < 0.001). [16] Marrie et al, found that coming from a chronic care facility or a nursing home was a major demographic associated with DNR upon admission, and more than half (53.8%) from institutions had a DNR order in place on admission [17]. This may reflect nursing home policies or a greater awareness among this group to have advanced directives.…”
Section: Living In Long-term Care Facilitiesmentioning
confidence: 99%
“…Our findings suggest a higher rate of DNAR use (31%) than identified in previous studies of similar conditions. Studies of patients admitted with community-acquired pneumonia reported rates of DNAR use ranging from 13% to 29%, [6-10] while studies in severe sepsis or septic shock reported rates ranging from 9% to 20%. [11-14] DNAR decisions in these studies were associated with older age, but conflicting findings were reported around the use of invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have estimated the prevalence of DNAR orders in patients admitted to hospital with community-acquired pneumonia [6-10] and sepsis,[11-14] and have attempted to identify factors associated with DNAR use, but we currently know very little about how DNAR orders have been used in people admitted with suspected COVID-19. The Pandemic Respiratory Infection Emergency System Triage (PRIEST) study was established to develop and evaluate triage tools for people presenting to hospital emergency departments with suspected COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have estimated the prevalence of DNACPR decision in patients admitted to hospital with community-acquired pneumonia 6 , 7 , 8 , 9 , 10 and sepsis, 11 , 12 , 13 , 14 and have attempted to identify factors associated with DNACPR use, but we currently know very little about how DNACPR decision have been used in people admitted with suspected COVID-19. The Pandemic Respiratory Infection Emergency System Triage (PRIEST) study was established to develop and evaluate triage tools for people presenting to hospital emergency departments with suspected COVID-19.…”
Section: Introductionmentioning
confidence: 99%